Removal Of Acid Orange 7 In Moving Bed Biofilm Reactor (Mbbr) With Polyhydroxyalkanoate (Pha) Pellets As The Biofilm Carrier - Chang, Jia Yun (2023)
Moving bed biofilm reactor utilizes both suspended and immobilized activated sludge to remediate wastewater. Selection and application of effective green materials as the biofilm carrier could reduce the production of secondary non-degradable polymer waste. This research aimed to assess the efficacy of biodegradable polyhydroxyalkanoate (PHA) pellets as the biofilm carrier to treat acid orange 7 (AO7).